PERAN ORANG TUA DALAM MENGONTROL PERGAULAN REMAJA DI DESA NCERA KABUPATEN BIMA - Uswatun Hasanah; Yuliatin Yuliatin; Sawaludin Sawaludin; Edy Kurniawansyah (Universitas Hamzanwadi, 2024)
The role of parents is essential in monitoring adolescents' social interactions. Parents bear full responsibility for supervising and managing adolescents' peer relationships. However, current conditions indicate that many parents are increasingly neglecting their roles and responsibilities due to factors such as busy schedules and other commitments. This situation has led to a decline in parental control over adolescents' social interactions. This studdy aims to analyze the implementation of parental roles in controlling adolescents' social interactions and identify the factors influencing these roles in Ncera Village. The research adopts a qualitative approach with a case study design. Informants were selected using purposive sampling, and data analysis involved data reduction, data presentation, conclusion drawing, and verification. The findings reveal that the implementation of parental roles in supervising adolescents' social interactions remains inadequate. Moreover, several factors influence the effectiveness of parental roles in Ncera Village, including parents' educational background, economic status, type of employment, availability of time, peer influence, and social media usage.